Pajak Daerah, Lain-Lain PAD yang Sah, dan Belanja Modal: Bukti Empiris Provinsi Sumatera Selatan - Rita Martini; Lesy Lorensa; Darul Amri (Jurnal Akademi Akuntansi, 2022)
This study aims to investigate the impact of local taxes and other legal municipal revenue on capital expenditures. The research population includes seventeen regencies/cities in the province of South Sumatra from 2015- 2019. Using the purposive sampling method, ten districts/cities were chosen as research samples. The Directorate General of Fiscal Balance (DJPK) website provided secondary data for Regency/City Budget Realization Reports. Multiple regression was employed in the data analysis, which was done with the SPSS program. The findings of the study show that local taxes have a significant impact on capital expenditures, other legitimate regional original income has a significant impact on capital expenditures, and both local taxes and other legitimate regional original income influence capital expenditures at the same time. According to this report, district/city governments in South Sumatra should improve regional income even more. Expanding economic streams and establishing self-sufficiency are required to achieve independence.